Maxim Violation In Real Steel Movie : A Pragmatics Approach - Nugraha, Risma Ardiansyah; , Drs. H. Maryadi, MA.; , Dra. Siti Zuhriah Ariatmi, M. Hum (2013)
This research aims at describing the violation of Grice Maxim‟s Cooperative Principle in conversation of Real Steel Movie. It‟s conducted in order to know what maxims which are violated by the characters of Real Steel Movie and the implicature of speaker‟s utterance when violating the maxims. The type of this research is descriptive qualitative, the several steps are done to analyze the data. In analyzing the kinds of maxims which are violated the steps are: describing the data in the form of dialogue, describing the context and analyzing how the characters used cooperative principle in his dialogue. In analyzing the implicature the steps are: describing the data in the form of dialogue and Describing the intended meaning of speaker utterance The study shows that 1) the maxim which often violated by the characters is maxim of Quality, as many as 9 data, Maxim Quantity is violated as many as 1 data, Maxim of Relation is violated as many as 5 data and Maxim of Manner is violated as many as 5 data. 2) The implicature of speaker‟s utterances are to convincing someone, to clarifying something, to refuse, to make a joke, and to shift the topic.